Mek Siti Industries (M) Sdn Bhd / Nurul Izzah Madihah Shafi'ai - Shafi'ai, Nurul Izzah Madihah (2022)
Mek Siti Industries (M) sdn bhd was incorporated in 2014 and was located at Jalan Bachok Kampung Beris Kubur Besar, Bachok, Kelantan. Mek siti is a factory that processes supplies wholesale and retail as well as provides self- branding product services for various types of instant premix flour such as Chocolate Cake Mix, red velvet cake mix and blue yellow cake mix. These products was very popular among women who love to make and sell cakes because it is easy to use and saves their time.